VARIANTS OF THE GENERALIZATION OF EPILEPTIC SEIZURES IN MESIAL TEMPORAL EPILEPSY IN ADULTS - V. О. Generalov; Т. R. Sadykov; Yu. ВV. Kazakova; Е. V. Amcheslavskaya (Эпилепсия и пароксизмальные состояния)
The purpose of work was to study polymorphism of kinematic variants of secondary generalized convulsive seizures by research of lesional and non-lesional mesial temporal epilepsy. For this purpose the patients suffering by non-lesional variants of mesial temporal epilepsy were analyzed: patients with epilepsy against chronic abusing alcohol (100 patients), patients with epilepsy against a chronic ischemia of a brain (62 patients) and patients with lesional mesial temporal epilepsy (with mesial temporal sclerosis, 31 patient). In a group with non-lesional mesial temporal epilepsy the main type of seizures were secondary generalized convulsive seizures with fast clinical generalization (91,4 %). In a group with lesional mesial temporal epilepsy the main type of seizures were secondary generalized convulsive seizures with slow clinical generalization (90,3 %). In addition discovered various clinic-encephalographic variants of generalization secondary generalized convulsive seizures: with slow clinical and slow encephalographic, slow clinical and fast encephalographic, with fast clinical and fast encephalographic, fast clinical and slow encephalographic generalization.